Enhanced MAC controller architecture for 2D processing based on FPGA with configurable resource allocation - Chiranjeevi G. N.; Subhash Kulkarni (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
The bulks of image processing algorithms are either two-dimensional (2D) or confined by their very nature. As a result, the 2D convolution function has a large impact on picture processing requirements. The methodology of 2D convolution and media access control (MAC) design can also be used to perform a variety of image processing tasks, and even as picture blurring, softening, and feature extraction. The main goal of this research is to develop a more efficient MAC control block-based 2D convolution architecture. This 2D algorithm can be implemented in hardware using fewer modules, multipliers, adders, and control blocks, resulting in significant hardware savings and look up table (LUT) reductions. The simulations were run in Verilog, and the Xilinx Vertex family field programmable gate array (FPGA) was used to build and test them. The recommended 2D convolution architectural solution is significantly faster and consumes significantly less hardware resources than the traditional 2D convolution implementation. The proposed architecture will result in technology that saves a substantial amount of processing time when it comes to LUTs.